The response of soil microbial diversity and abundance to long-term application of biosolids - Mossa, Abdul-Wahab; Dickinson, Matthew J.; West, Helen M.; Young, Scott D.; Crout, Neil M.J. (Elsevier, 2017)
The disposal of biosolids poses a major environmental and economic problem. Agricultural use is generally regarded as the best means of disposal. However, its impact on soil ecosystems remains uncertain. Biosolids can improve soil properties by supplying nutrients and increasing organic matter content but there is also a potentially detrimental effect arising from the introduction of heavy metals into soils. To assess the balance between these competing effects on soil health, we investigated soil bacterial and fungal diversity and community structure at a site that has been dedicated to the disposal of sewage sludge for over 100 years. Terminal restriction fragment length polymorphism (T-RFLP) was used to characterize the soil microbial communities. The most important contaminants at the site were Ni, Cu, Zn, Cd, and Pb. Concentrations were highly correlated and Zn concentration was adopted as a good indicator of the overall (historical) biosolids loading. A biosolids loading, equivalent to 700–1000 mg kg−1 Zn appeared to be optimal for maximum bacterial and fungal diversity. This markedly exceeds the maximum soil Zn concentration of 300 mg kg−1permitted under the current UK Sludge (use in agriculture) Regulations. Redundancy analysis (RDA) suggested that the soil microbial communities had been altered in response to the accumulation of trace metals, especially Zn, Cd, and Cu. We believe this is the first time the trade-off between positive and negative effects of long term (>100 years) biosolids disposal on soil microorganisms have been observed in the field situation.